Cardiac tamponade and acute renal failure following Salmonella agona pericarditis. Issue 619 (May 1977) - Webster, J.; Petersen, J.; Edward, N.
Abstract : A 19-year-old female presented with cardiac tamponade complicated by acute renal failure. Salmonella agona was cultured from pericardial aspirate after repeated pericardiocentesis in several sites. Treatment with ampicillin and intermittent haemodialysis led to complete recovery.